Thermal degradation kinetics and lifetime estimation of orthophthalic unsaturated polyester resins. - Villa, Ralph P. et al (UPCOE NEC Technical Bulletin)
In this study, the model-free isoconversional methods of Vyazovkin, Ozawa-Flynn-Wall (OFW) and Kissinger-Akahira-Sunose (KAS) together with the master-plot method were used to study the non-isothermal thermal degradation kinetics of orthophthalic unsaturated polyester (ortho-UP). Non-isothermal experiments at four different heating ares (2, 5, 10 and 20 K/min) were conducted using thermogravimetric analysis (TGA). The experimental data was used to find the kinetic parameters (E, A and f(α) of this process. The dependence of the activation energy E with conversion, α were determined using the three isoconversional models. Likewise, the pre-exponential factor A and reaction model f(α) (or g(α)) were obtained using the master-plot method. Results show that the activation energy and pre-exponential factor for the thermal degradation of ortho-UP are E= 144.036 kJ/mol and A= 1.4595 x 10¹⁰ min ¯¹, respectively. A three-dimensional diffusion model, of the form, g(α)= [1-(1-α)¹´³]², was determined to be the best kinetic model for this particular system. The consistency of the kinetic triplets (E, A, and g(α)) were checked by comparing experimental and calculated α-T curves.